A note on minor antichains of uncountable graphs. Issue 3 (3rd September 2022) - Pitz, Max
Abstract: A simplified construction is presented for Komjáth's result that for every uncountable cardinal κ κ , there are 2 κ 2^κ graphs of size κ κ none of them being a minor of another.